Determination of production losses related to lumpy skin disease among cattle in Turkey and analysis using SEIR epidemic model - Mat, Burak; Arikan, Mehmet Saltuk; Akin, Ahmet Cumhur; Cevrimli, Mustafa Bahadir; Yonar, Harun; Tekindal, Mustafa Agah (Bmc, 2021)
Background Lumpy Skin Disease (LSD) is an infectious disease induced by the Capripoxvirus, causing epidemics in Turkey and several countries worldwide and inducing significant economic losses. Although this disease occurs in Turkish cattle every year, it is a notifiable disease. In this study, LSD in Turkey was modelled using the Susceptible, Exposed, Infectious, and Recovered (SEIR) epidemiological model, and production losses were estimated with predictions of the course of the disease. The animal population was categorized into four groups: Susceptible, Exposed, Infectious, and Recovered, and model parameters were obtained. The SEIR model was formulated with an outbreak calculator simulator applied for demonstration purposes. Results Production losses caused by the LSD epidemic and the SEIR model's predictions on the disease's course were evaluated. Although 1282 cases were identified in Turkey during the study period, the prevalence of LSD was calculated as 4.51%, and the mortality rate was 1.09%. The relationship between the disease duration and incubation period was emphasized in the simulated SEIR model to understand the dynamics of LSD. Early detection of the disease during the incubation period significantly affected the peak time of the disease. According to the model, if the disease was detected during the incubation period, the sick animal's time could transmit the disease (Tinf) was calculated as 2.66 days. Production loss from LSD infection was estimated at US $ 886.34 for dairy cattle and the US $ 1,066.61 for beef cattle per animal. Conclusion Detection of LSD infection during the incubation period changes the course of the disease and may reduce the resulting economic loss.
Keywords: Epidemiology; SEIR Model; Lumpy Skin Disease; production losses; Turkey